Numerical Analysis of the Susceptible Exposed Infected Quarantined and Vaccinated (SEIQV) Reaction-Diffusion Epidemic Model - Ahmed, Nauman; Fatima, Mehreen; Baleanu, Dumitru; Nisar, Kottakkaran Sooppy; Khan, Ilyas; Rafiq, Muhammad; Rehman, Muhammad Aziz ur; Ahmad, Muhammad Ozair (Frontiers in Physics, 2020)
In this paper, two structure preserving nonstandard finite difference (NSFD) operator splitting schemes are designed for the solutions of reaction diffusion epidemic models. The proposed schemes preserve all the essential properties possessed by the continuous systems. These schemes are applied on a diffusive SEIQV epidemic model with saturated incidence rate to validate the results. Furthermore, stability of the continuous system is proved and bifurcation value is evaluated. Comparison is also made with the existing operator splitting numerical scheme. Simulations are also done for numerical experiments.